Sub-seasonal and seasonal climate predictions for a sporting goods retailer company: Co-development of a climate service from scratch - Albert Soret; Albert Martínez-Botí; Raul Marcos-Matamoros; Nube Gonzalez-Reviriego; Francesc Roura-Adserias; Lluís Palma; Sergio Benito Martín; Sergio González-Ubierna (Climate Services)
Predicting variations in weather conditions beyond a few days is of great interest to decision-makers, as this time horizon aligns with the strategic planning needs of stakeholders in climate-vulnerable sectors affected by seasonality. While the effects of climate variability are well understood in sectors such as energy and agriculture, where the potential applications of climate predictions in decision-making are already being explored, in other sectors, the direct impacts of climate variability on operations or on defining seasonal transitions remain unclear. In this context, our paper describes the knowledge exchange and co-development process carried out during the co-production of an operational climate service for a sports retail company. We developed a climate service that combines sub-seasonal and seasonal forecasts to provide tailored and user-friendly climate information for the upcoming weeks and months. The operational system supported decision-making in selected stores over a year, with regular evaluations helping to build trust in the service and informing new developments for an improved version. This study demonstrates that a co-production approach, where interaction between the user and the scientist is established early in the forecast product development, is fundamental to the creation of a successful climate service. Beyond this specific case, the long-term aim of the work is to compile and synthesise the lessons learned in developing this service at sub-seasonal and seasonal timescales, to encourage its adoption in other comparable retail businesses also affected by climate variability (e.g. the fashion industry and food-snack production).